2011
DOI: 10.4111/kju.2011.52.9.607
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Chemokine Receptor CXCR4 Expression and Prognostic Factors in Patients with Prostate Cancer

Abstract: PurposeWe evaluated the correlation between the expression of CXCR4 and prognostic factors in patients with prostate cancer.Materials and MethodsA total of 57 patients who had undergone surgery for prostate cancer were enrolled. Specimens were obtained before any treatment and were stained with antihuman CXCR4 antibody. The intensity of staining was graded as low or high. The age, pretreatment prostate-specific antigen (PSA) level, Gleason score, T stage, biochemical recurrence, local recurrence, and distant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 21 publications
(22 reference statements)
0
31
0
Order By: Relevance
“…Hematological malignancy (7 studies, 764 patients) [12-18], breast cancer (18 studies, 4125 patients) [10, 11, 19-34], colorectal cancer (7 studies, 515 patients) [35-41], esophageal cancer (7 studies, 886 patients) [42-48], gastric cancer (5 studies, 755 patients) [49-53], head and neck cancer (7 studies, 577 patients) [54-60], renal cancer (6 studies, 764 patients) [61-66], lung cancer (7 studies, 727 patients) [8, 67-72], melanoma (4 studies, 168 patients) [73-76], gynecologic cancer (8 studies, 826 patients) [9, 77-83], pancreatic cancer (2 studies, 320 patients) [84, 85], prostate cancer (2 studies, 109 patients) [86, 87], liver cancer (2 studies, 256 patients) [88, 89], sarcoma (2 studies, 168 patients) [90, 91] and gallbladder cancer (1 study, 72 patients) [92] were evaluated in current meta-analysis as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hematological malignancy (7 studies, 764 patients) [12-18], breast cancer (18 studies, 4125 patients) [10, 11, 19-34], colorectal cancer (7 studies, 515 patients) [35-41], esophageal cancer (7 studies, 886 patients) [42-48], gastric cancer (5 studies, 755 patients) [49-53], head and neck cancer (7 studies, 577 patients) [54-60], renal cancer (6 studies, 764 patients) [61-66], lung cancer (7 studies, 727 patients) [8, 67-72], melanoma (4 studies, 168 patients) [73-76], gynecologic cancer (8 studies, 826 patients) [9, 77-83], pancreatic cancer (2 studies, 320 patients) [84, 85], prostate cancer (2 studies, 109 patients) [86, 87], liver cancer (2 studies, 256 patients) [88, 89], sarcoma (2 studies, 168 patients) [90, 91] and gallbladder cancer (1 study, 72 patients) [92] were evaluated in current meta-analysis as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled model showed a significantly shorter OS with CXCR4 over-expression patients in hematological malignancy (7 studies, 764 patients, HR=1.93, 95% CI, 1.33-2.79, Figure 10) [12-18], breast cancer (18 studies, 4125 patients, HR=1.58, 95% CI, 1.29-1.94, Figure 11) [10, 11, 19-34], colorectal cancer (5 studies, 375 patients, HR=1.83, 95% CI, 1.32-2.53, Figure 12) [36, 37, 39-41], esophageal cancer (7 studies, 886 patients, HR=1.65, 95% CI, 1.24-2.19, Figure 13) [42-48], head and neck cancer (7 studies, 577 patients, HR=2.02, 95% CI, 1.37-2.97, Figure 14) [54-60], renal cancer (5 studies, 594 patients, HR=2.93, 95% CI, 2.06-4.15, Figure 15) [61, 62, 64-66], lung cancer (6 studies, 573 patients, HR=2.51, 95% CI, 1.64-3.83, Figure 16) [8, 67-69, 71, 72], gynecologic cancer (7 studies, 796 patients, HR=2.24, 95% CI, 1.11-4.50, Figure 17) [9, 77-82], liver cancer (2 studies, 256 patients, HR=2.75, 95% CI, 2.02-3.75) [88, 89], prostate cancer (2 studies, 109 patients, HR=2.67, 95% CI, 1.61-4.42) [86, 87] and gallbladder cancer (1 studies, 72 patients, HR=2.30, 95% CI, 1.10-4.80) [92]. Based on the available data, the associations between CXCR4 over-expression and PFS were inconclusive in gastric cancer (5 studies, 755 patients, HR=1.94, 95% CI, 0.86-4.35, Figure 18) [49-53], melanoma (3 studies, 136 patients, HR=1.93, 95% CI, 0.88-4.25, Figure 19) [74-76], pancreatic cancer (2 studies, 320 patients, HR=1.34, 95% CI, 0.63-2.83) [84, 85] and sarcoma (2 studies, 168 patients, HR=5.14, 95% CI, 0.64-41.50) [90, 91].…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that cancerous CXCL12 positivity was determined to be an independent prognostic factor for patient survival of gastric cancer [11]. CXCR4 has also been found to be a prognostic marker in various types of cancer, including acute myeloid leukemia [12], breast cancer [13], and prostate cancer [14]. However, a comprehensive analysis of CXCR4 expression in relation to survival of patients with gastric cancer remains largely unknown and needs to be further established.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that CXCR4-expressing tumor cells metastasize to SDF-1α-secreting distant organs via the CXCR4–SDF-1α pathway [22]. Therefore, the evaluation of CXCR4/SDF-1α expression level may have a significant prognostic value in various types of malignancies, because the high expression of CXCR4 or SDF-1α has been shown to predict poor survival outcomes in colon [24], pancreatic [25], prostate [26], breast [27], ovarian [28], and lung cancer patients [29]. Furthermore, blocking the interaction between CXCR4 and SDF-1α is supported by the available data as an effective therapeutic strategy that would interfere with the metastatic and tumorigenic potentials of diverse types of malignancies.…”
Section: Introduction: Physiological and Pathologic Functions Of Cxcrmentioning
confidence: 99%